1995
DOI: 10.1084/jem.182.4.1067
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine interactions in human immunodeficiency virus-infected individuals: roles of interleukin (IL)-2, IL-12, and IL-15.

Abstract: SummaryCytokines have been shown to be powerful regulators of the immune response. In this study, we analyze the effect that the newly recognized cytokine interleukin (IL)-15 has on proliferation and cytokine induction using peripheral blood mononuclear cells (PBMCs) and purified CD4 § T cells from patients infected with human immunodeficiency virus (HIV) who are at various stages in their disease. We observed that IL-15 enhances the proliferative response in a dose-dependent manner from PBMCs of HIV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 32 publications
8
66
2
Order By: Relevance
“…Since clinical trials have shown HAT to be an effective therapy in both these settings, we focused on the mechanism(s) by which HAT inhibits IFN-␥ production. Earlier studies had noted that anti-Tac inhibits IFN-␥ production from T cell clones or PHA-stimulated PBMC but did not explore the basis of this inhibition (21,22). In our studies, intracellular cytokine staining at the peak of IFN-␥ production (48 h) revealed that HAT inhibits IFN-␥ expression in both CD4 and CD8 T cells, independent of CD28 costimulation.…”
Section: Discussionsupporting
confidence: 50%
“…Since clinical trials have shown HAT to be an effective therapy in both these settings, we focused on the mechanism(s) by which HAT inhibits IFN-␥ production. Earlier studies had noted that anti-Tac inhibits IFN-␥ production from T cell clones or PHA-stimulated PBMC but did not explore the basis of this inhibition (21,22). In our studies, intracellular cytokine staining at the peak of IFN-␥ production (48 h) revealed that HAT inhibits IFN-␥ expression in both CD4 and CD8 T cells, independent of CD28 costimulation.…”
Section: Discussionsupporting
confidence: 50%
“…IL-15 itself induces in vitro antigen-independent expansion of human naive CD8 + T cells [18] and enhances antigen-specific proliferation of T cells isolated from HIV-infected patients [19]. Yet, the mere action of soluble IL-15 cannot explain the enhanced priming by IL15-DC, as the preferential expansion of CD8 + T cells depends upon cell-cell contact.…”
Section: Discussionmentioning
confidence: 98%
“…Both cytokines are therefore mutually exclusive in their production in various cell types [34]. Even though their amino acid sequence shows no homology [34,36], the biological action of both proteins seems to be similar as activators of CD4 + and CD8 + T lymphocytes, gd T cells, NK cells and B lymphocytes [40][41][42][43][44][45][46]. This could be explained by the observation that both IL-2 and IL-15 bind to the IL-2R b-and g cchain [34,36].…”
Section: Introductionmentioning
confidence: 99%